Comparación entre un sistema neuro difuso auto organizado y un modelo ARIMAX en la predicción de series económicas volátiles - Avellaneda González, José Alejandro; Ochoa Rey, Cynthia María; Figueroa García, Juan Carlos (Ingeniería, 2012)
This paper presents the selection of a volatile share from Colombian Stock Exchange, which is analyzed using ARIMAX (autoregressive integrated moving average with exogeneous input) and SONFS (self organizing neural fuzzy sytem) models. These methods are compared using three features: the MAE (mean absolute error), residuals as a white noise process and the AIC (Akaike Information Criterion).